Optimisation of cultivation conditions for Bacillus velezensis G7 from mangrove plants and exploration of potential bacteriocins - Li, Yang; Ma, Haotian; Pan, Ruixue; Long, Yuner; Zhao, Yining; Yu, Mengbo; Peng, Jinju; Ma, Yi (Frontiers in Pharmacology, 2025)
IntroductionBacteriocin P7 was extracted from the cell-free supernatant (CFS) of Bacillus velezensis G7, which is a strain isolated from mangrove plants.MethodsIn this study, the culture conditions of B. velezensis G7 were optimised using an orthogonal test. The (CFS) was subsequently purified by using TA-GF75 gel chromatography, Tiderose Q HP anion chromatography and reversed-phase high-performance liquid chromatography (RP-HPLC). Finally, the bacteriocin was identified by using LC-MS/MS.Results and discussionThe optimal culture conditions for B. velezensis G7 are 4.5 g/100 mL glucose, 1.5 g/100 mL yeast, and 1.2 g/100 mL MgSO4·7H2O. The stability of the CFS is affected by several factors, including heat, UV treatment and different storage conditions. High temperatures and long UV irradiation treatments significantly reduce the stability of CFS, which is more sensitive to strong acids, bases and enzymatic degradation. The minimum inhibitory concentration (MIC) of purified bacteriocin P7 against S. aureus was determined to be 30.352 μg/mL. On the basis of the results of the haemolytic activity assay, it was concluded that the use of bacteriocin P7 at concentrations equal to or below the 2 × MIC is safe. The addition of organic solvents and inorganic salts did not affect the bacteriocin P7, while the incorporation of SDS could enhance its antimicrobial efficacy. The bacteriocin was subjected to analysis by LC-MS/MS, which revealed that it was similar to the class I bacteriocin amyloliquecidin GF610. The findings of the present study indicate that the endophytic B. velezensis G7 from mangrove plant can produce bacteriocins, thereby providing a reference point for the expansion of novel bacteriocin sources.